Regeneration Analysis of Bone Char Used in Water Defluoridation: Chemical Desorption Route, Surface Chemistry Analysis and Modeling - Herson Antonio González-Ponce; Didilia Ileana Mendoza-Castillo; Adrián Bonilla-Petriciolet; Hilda Elizabeth Reynel-Ávila; Karla Iveth Camacho-Aguilar (International Journal of Chemical Engineering)
High concentrations of fluoride (F−) in drinking water represent a public health threat, and consequently, effective and sustainable methods are required to improve the water quality, mainly in developing and low-income countries. This study focused on the thermodynamics of fluoride adsorption on bone char regenerated with NaOH for water defluoridation. A detailed analysis of the number of fluoride adsorption/desorption cycles, their impact on the performance and surface chemistry of bone char using different NaOH concentrations, and modeling of the adsorption mechanism using statistical physics theory was carried out. The results showed that 0.075 mol/L NaOH was effective in recuperating the defluoridation properties of bone char with a regeneration efficiency higher than 90% during five adsorption/desorption cycles. Bone char regeneration efficiency decreased up to 64% after ten adsorption/desorption cycles with a maximum fluoride adsorption capacity of 0.18 mmol/g. NaOH restored the bone char surface properties for ligand exchange of the fluoride anions via the hydroxyapatite functionalities contained in this adsorbent. It was calculated that around 0.25–0.46 mmol/g hydroxyapatite ligand exchange sites of regenerated bone char samples could be involved in the fluoride adsorption, which was also expected to be a mono-ligand mechanism. The reduction in defluoridation properties of bone char during the regeneration cycles was attributed to the decrease in the ligand exchange capacity as well as the deactivation and blocking of some functional groups of hydroxyapatite, which limited their participation in consecutive adsorption processes. This study contributes to the optimization of the recycling and reuse of bone char for fluoride removal from water to reduce the operating defluoridation costs, thus enhancing the application of this technology in low-income areas where fluorinated water represents a threat to public health.